2018
DOI: 10.1002/cmdc.201800282
|View full text |Cite
|
Sign up to set email alerts
|

Toward Angiogenesis Inhibitors Based on the Conjugation of Organometallic Platinum(II) Complexes to RGD Peptides

Abstract: A novel conjugate between a cyclometalated platinum(II) complex with dual antiangiogenic and antitumor activity and a cyclic peptide containing the RGD sequence (-Arg-Gly-Asp-) has been synthesized by combining solid- and solution-phase methodologies. Although peptide conjugation rendered a non-cytotoxic compound in all tested tumor cell lines (± α β and α β integrin receptors), the antiangiogenic activity of the Pt-c(RGDfK) conjugate in human umbilical vein endothelial cells at sub-cytotoxic concentrations op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The development of bioactive metallodrugs with dual cytotoxic and antiangiogenic properties holds promise as an alternative to classical cisplatin‐based drugs in chemotherapy. To this aim, Marchán, Ruiz and colleagues [42] proposed the synthesis and biological evaluation of a robust covalent conjugate (compound 7 , Scheme 4) embodying the cilengitide analogue c (RGDfK) and the cyclometalated Pt(II)‐DMBA complex, which had previously demonstrated to display antiangiogenic and antitumor activities at sub‐micromolar concentrations [43] . Unfortunately, cytotoxicity studies in vitro revealed that conjugation to the RGD peptide resulted in a dramatic decrease of antiproliferative activity with respect to the unconjugated Pt‐DMBA complex reference, while the antiangiogenic activity was retained at sub‐cytotoxic concentrations and was similar to that of reference cyclopeptide c (RGDfK) alone.…”
Section: Dual Conjugates Embedding Noncleavable Linkersmentioning
confidence: 99%
“…The development of bioactive metallodrugs with dual cytotoxic and antiangiogenic properties holds promise as an alternative to classical cisplatin‐based drugs in chemotherapy. To this aim, Marchán, Ruiz and colleagues [42] proposed the synthesis and biological evaluation of a robust covalent conjugate (compound 7 , Scheme 4) embodying the cilengitide analogue c (RGDfK) and the cyclometalated Pt(II)‐DMBA complex, which had previously demonstrated to display antiangiogenic and antitumor activities at sub‐micromolar concentrations [43] . Unfortunately, cytotoxicity studies in vitro revealed that conjugation to the RGD peptide resulted in a dramatic decrease of antiproliferative activity with respect to the unconjugated Pt‐DMBA complex reference, while the antiangiogenic activity was retained at sub‐cytotoxic concentrations and was similar to that of reference cyclopeptide c (RGDfK) alone.…”
Section: Dual Conjugates Embedding Noncleavable Linkersmentioning
confidence: 99%
“…However, although promising, metal complexes are generally only less developed as pharmaceutics owing to their poor water solubility and limited cellular uptake [30] . One way to overcome these issues is the combination of metal complexes with bioactive peptides, which has gained considerable attention during the last decade [31–41] . In this context, so‐called cell‐penetrating peptides (CPPs) are promising tools to deliver metal complexes into various types of cells [41–49] .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of tumor-induced angiogenesis, transmembrane receptors such as integrins (α v β 3 and α v β 5 ) are highly expressed, which have a very high affinity for peptides containing RGD (Arg-Gly-Asp) and NGR (Asn-Gly-Arg) sequences. In this regard, complex 26 ( Figure 10) with dual antiangiogenic and antitumor activity was a non-cytotoxic compound with IC 50 >100 µM in different cancer cell lines (± α v β 3 and α v β 5 integrin receptors), while showing the antiangiogenic activity in HUVECs at sub-cytotoxic concentrations [89], which exemplified the design of angiogenesis inhibitors through conjugating a metallodrug with antiangiogenic activity to a cyclic RGD-containing peptide or a peptidomimetic analogue. Targeting angiogenesis provides an alternative direction for tumor-targeting therapy [90].…”
Section: Targeted Monofunctional Pt II Complexesmentioning
confidence: 99%